Data visualisation: A handbook for data driven design - Kirk, Andy (New Delhi Sage, 2025)
This handbook offers everything students and scholars need to master the craft of developing insightful and delightful data visualisations. Across over 300 pages packed full of useful knowledge this book is an essential reference to help readers harness the wide range of contextual, analytical, editorial, and visual ingredients that shape this complex but invigorating subject.